A Review on the Concept (Challenges and Opportunities) of One Health Approach to Control Emerging and Re-Emerging Zoonosis - Fayisa, Wakgari Oljira (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2023)
Zoonotic diseases are infectious diseases that are naturally transmitted from vertebrate animals to humans and vice versa. They are caused by all types of pathogenic agents, including bacteria, parasites, fungi, viruses, and prions. Infectious diseases have for centuries ranked with wars and famine as major challenges to human health and survival. Emerging and re-emerging zoonotic diseases negatively affect the human and animal populations. The One Health approach has a great role; it needs strong collaborative efforts and interdisciplinary communication to prevent epidemics or epizootic diseases and to maintain ecosystem integrity, thereby improving and defending optimal health around the globe. Despite this potential, failure to work collaboratively, lack of awareness, absence of a standardized framework to capture the concept of disciplines, and other problems with the difficulty of wildlife management had a negative impact on one health implementation. However, with changes in the environment, human behavior, and habitat, these infections are increasingly emerging from wildlife species. By solving the challenges of one health approach, it is possible to make it a more powerful tool to protect living things and the environment from diseases around the globe. Therefore, all concerned bodies should participate in one health activity to achieve the future expected of one health approach. Although this review focuses on approaches to challenge control of emerging and re-emerging zoonotic diseases.